Liver morphological changes and proinflammatory cytokines in experimental animals in case of cirrhosis - O. I. Romak; Yu. Sadovska; I. Goryuk (Kazimierz Wielki University, 2017)
Liver cirrhosis is one of the acute problems of modern hepatology that develops in case of long-term chronic hepatitis. It is known that cytokines play an important role in controlling an adaptive response to chronic toxic damage. After the morphological examination of the hepatic tissue and of the proinflammatory cytokine system in case of experimental cirrhosis it was established the prominent immune response to acute inflammation at early stage as well as pro-inflammatory interleukins level significant increase. The further pathomorphological examination showed a minor involution of the pathological process, the immune response was also slightly inhibited in comparison to the previous period.